Maintaining Maternal and Child Health from an Early Age: The Foundation of a Healthy Future Generation - Juwita; Rizqy Wahyuni Imran (Universitas Muhammadiyah Palu, 2025)
Maternal and child health is a crucial factor in achieving a healthy and high-quality generation. Early health maintenance serves as a strategic effort to prevent nutritional problems, diseases, and complications that may have long-term impacts on child development. This article discusses the importance of health education for pregnant women, balanced nutrition, regular health check-ups, and the role of families and communities in supporting maternal and child health programs. An integrated approach involving healthcare workers, government, and society is essential to build awareness and healthy lifestyles. Maintaining maternal and child health from an early age is expected to create a strong, productive, and competitive future generation.